Keberadaan Pekerja Anak di Indonesia - Fatih Nurfaiz, Agil (Fakultas Syariah dan Ekonomi Islam, 2023)
Child labor is a phenomenon that is often found in society, this phenomenon still occurs today even though there is a prohibition against employing children in Law no. 13 of 2003 concerning Manpower. Various reasons are mentioned why they work both because of poverty and social. With these reasons the rights that should be obtained by children are lost and children grow up without being able to enjoy these rights. In practice in society, child workers do not always receive fair treatment and receive comfortable conditions for work, ranging from low wages to labor exploitation experienced by child workers. child labor is enforced. The existence of various laws related to child labor can provide certainty in efforts to protect child labor in Indonesia